Hot Spot mapping - A spatial and methodological approach to analyzing outdoor crimes in Malmö. - Holm,Jimmy (2018)
This thesis aim to visualize and explore the methodological approach to finding the spatial patterning of crime through a geographical information system as a means for future guidance within spatial crime analysis. The analysis was applied to outdoor crimes for the city of Malmö in the year 2007. As a means for conducting this analysis a casestudy is performed. Both as a review of current police-methodology within crimepreventive work and on two individual geographic locations. After gathering and sorting of data a total of 9876 crime incidents was analysed. Two spatial analyses are performed, the Optimized Hot Spot-analysis tool and the Kernel Density Estimationanalysis tool. The Average Nearest Neighbor-model was applied to the data for further statistical accuracy. The thesis concludes that both tools have their usages. The optimized hot spot analysis was concluded to be of most use when the study area was large whereas the kernel density estimation analysis performed better for finding small variations on smaller study areas. However, they are the most efficient as complementary tools rather than when used as a single-method approach.